POPULASI DAN TINGKAT SERANGAN SPODOPTERA FRUGIPERDA PADA TANAMAN JAGUNG DI DESA TULO KABUPATEN SIGI - Arfan; If'all; Jumardin; Hasmari Noer; Sumarni (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2020)
Spodoptera frugiperda is a new pest in Central Sulawesi attacks maize crops. It was reported in 2019, known in Sigi, Donggala, Touna, Bangga, Tolitoli, Buol, and Palu City Regencies. Also, this pest is spreading rapidly by threatening maize production in Central Sulawesi. This study aims to measure the population and intensity of Spodoptera frugiperda attacks on maizes in Tulo Village, Dolo Sub-district, Sigi Regency. The study, conducted from January to March 2020, used a survey method and selected sampling. Our location takes each plot measuring 2x2 m. Population observations were carried out by collecting larvae found in the sample plants. The attack's intensity was carried out by counting the number of leaves showing symptoms of an attack on the top leaves. Calculation of the proportion of attacks was carried out by the Davis method. The results showed that the highest S. frugiperda population at the age of 14 days after planting. The intensity of S. frugiperda attack on maize was relatively high at the age of 42 days after planting, with an average attack of 65.24%. Climatic data during this period, an average of 28.76-29.43 ℃ with air influence was 71.1-72%.